Dataset on wastewater quality monitoring with adsorption and reflectance spectrometry in the UV-vis range - Pierre Lechevallier; Günter Gruber; Vojtěch Bareš; Nicolas Neuenhofer; Laura Waldner; Abhinit Mahajan; Lena Mutzner; Jörg Rieckermann (Scientific Data)
Abstract A major challenge in wastewater and sewer system monitoring is the development of advanced sensing technologies to improve standard pollutant measurement and allow real-time online detection of emerging contaminants. This study presents a dataset from a 25-week measurement campaign comparing a novel hyperspectral imaging system to state-of-the-art ultraviolet-visible (UV-vis) sensors. The dataset includes 5801 hyperspectral images of raw wastewater, measurements of temperature, ammonium, flow, turbidity, pH, and UV-vis absorbance spectra, as well as 533 grab samples analyzed for conventional pollutants. We also gathered 86 samples after four rain events and analyzed them for twenty organic chemicals, providing insights into the impact of wet weather on pollutant levels. The data collection and processing methodologies are detailed, along with visualizations and analysis. Despite difficulties in the maintenance of some sensors, in particular the ion-selective electrode for ammonium measurement, the dataset’s high temporal resolution, the time span of 25 weeks, and the extensive range of analyzed pollutants make it a valuable resource for advancing the field of urban water management.